Pendekatan STEAM Berbasis Kearifan Lokal dalam Pembelajaran IPS untuk Meningkatkan Kemampuan Pemecahan Masalah Sosial Siswa SMP - Sisilia Wulan Riviani; Bayu Pratama; Habibullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to conceptually analyze the implementation of the Ethno-STEAM approach, which integrates Science, Technology, Engineering, Arts, and Mathematics (STEAM) with local wisdom, in enhancing junior high school students' social problem-solving skills in Social Studies (IPS) learning. This study employed a library research method using a content analysis approach to examine credible scholarly literature published between 2012 and 2025. The findings indicate that the implementation of Ethno-STEAM enhances students' social problem-solving skills through four main mechanisms: (1) fostering meaningful contextual learning, (2) developing integrative thinking, (3) strengthening cultural intelligence, and (4) improving collaboration and communication skills. Furthermore, this study proposes a conceptual pedagogical model consisting of five stages—Explore, Analyze, Design, Implement & Communicate, and Reflect & Evaluate—as a framework for implementing Ethno-STEAM in Social Studies learning. The study concludes that the Ethno-STEAM approach provides an effective, relevant, and contextual learning solution for junior high school Social Studies by integrating STEAM with local wisdom, thereby creating more meaningful learning experiences, promoting authentic social problem-solving, and aligning with the implementation of the Merdeka Curriculum and the strengthening of the Pancasila Student Profile. Keywords: Ethno-STEAM, Junior High School, Local Wisdom, Social Problem-Solving; Social Studies Learning, STEAM.